2013
DOI: 10.1039/c3sm51736e
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle self-assembly moderated by a cholesteric liquid crystal

Abstract: International audienceWe show that the study of gold nanoparticle self-assemblies induced by a liquid crystal matrix reveals the intimate distorted structure of the liquid crystal existing prior to nanoparticles incorporation. We also show how this intimate structure monitors the spacing between nanoparticles in the self-assemblies. We have created hybrid films of cholesteric liquid crystal (CLC) and gold nanoparticles, the CLC being deformed by competing anchorings at its two interfaces. Whereas previous resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 46 publications
2
34
1
1
Order By: Relevance
“…Acc. Lincei similar to the one obtained with the same NPs embedded in a cholesteric matrix (Pendery et al 2013). In cholesteric LCs, the LC matrix induces a compression, leading to s ¼ 0:6 nm.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Acc. Lincei similar to the one obtained with the same NPs embedded in a cholesteric matrix (Pendery et al 2013). In cholesteric LCs, the LC matrix induces a compression, leading to s ¼ 0:6 nm.…”
Section: Discussionsupporting
confidence: 50%
“…k LSPR ¼ 516 nm in toluene. Their synthesis is described elsewhere (Pendery et al 2013). The solution was deposited on the substrate and left evaporating (for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…14 So far efforts to obtain chiral nematics filled with NPs have either relied on adding hydrocarbon groupcapped NPs to a chiral nematic matrix or, alternatively, on functionalizing gold NPs with chiral groups and dispersing them in a nematic liquid crystal. 15,16,17,18,19,20,21,22 In the main it has been found that NPs aggregate in the defects of the LC texture. This is possibly mediated by the pinning of features of defects such as fingerprint or schlieren textures to surfaces, providing thus a means of spatial NP assembly.…”
mentioning
confidence: 99%
“…[36,[43][44] This aggregation is due to the distortions and disorder induced in the liquid crystal around most of the nanoparticles, which become reduced if the nanoparticles are aggregated. [36,45] In nematic liquid crystals, the best method to prevent aggregation of nanorods is to graft specific ligandsaround the nanorodsin order to allow for a weak anchoring of the liquid crystal molecules. [46,47] Weak anchoring indeed prevents the formation of liquid crystal defects and thus prevents aggregation.…”
mentioning
confidence: 99%